Bilateral Congenital Cystic Eye Posterior to the Lower Eyelid: Case Report - Doganay, Selim; Alkan, ALPAY; ALKAN, ALPAY; ÇANKAYA, CEM; Firat, Penbegul (My University, 2012)
One day after delivery, an infant boy was referred to our clinic with the complaint of bilateral inferior eyelid bluish discoloration and absence of globe in orbital space. External ocular examination showed no globe in orbital space but a mild bulging of the right and left lower eyelid with an area of bluish discoloration. There were no other ocular or non-ocular abnormalities. Systemic evaluation was normal. Magnetic resonance imaging (MRI) confirmed presence of bilateral cystic eye and absence of ocular structures in orbital space. MRI at age of 14 months showed enlargement of the left cystic eye. A clear fluid (5 cc) was aspirated from the cyst to restore the globe size within the lower eyelid. Biochemical analysis of cystic fluid revealed no abnormalities.